A THREE YEAR STUDY ON THE ELECTROPHORETIC PATTERNS OF SERUM PROTEINS WITH SPECIAL REFERENCE TO VARIOUS GLOBULINOPATHIES IN SAUDIS - Wahid, Mukhtar Ahmad; Abraham, George Kuruppacheril (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT Human sera comprising 545 specimens spread over a period of three years were analyzed electrophorctically for proteins. Only 159 samples (29%) exhibited abnormal serum protein patterns. They were in the order of inflammatory disorders (acute/chronic), 60 (37.7%), Polyclonal gammopathies,48 (30.1%), Cirrhosis, 22 (13.8%), Monoclonal gammopathies, 22 (13.8%), Agammaglobulinemia, 3 (1.9%), Nephrosis, 2 (1.2%), Protein-losing enteropathy, 1 (0.6%), Lowalpha 1 -antitrypsin, 1 (0.6%), Inflammatory diseases of various nature, therefore, constitute the major serum protein abnormalities in Riyadh. Moreover, their occurrence varies with age, sex and climatic conditions as elsewhere in the world.